Efeito do gengibre (zingiber officinale) no controle glicêmico e lipêmico de pessoas com diabetes tipo 2: ensaio clínico randomizado duplo cego controlado por placebo - Carvalho, Gerdane Celene Nunes (2018)
Diabetes Mellitus glycemic control is a challenge in clinical practice. In addition, diabetes predisposes to diabetic dyslipidemia. For the reduction of glycemic and lipemic levels in people with type 2 diabetes, phytotherapy is an alternative for adjuvant treatment. The aim of this study was to evaluate the effectiveness of ginger (Zingiber officinale) in reducing glycemic and lipemic level. This is a randomized, double-blind, placebo-controlled clinical trial conducted in nine Family Health Strategies on Picos, Piauí. The sample consisted of 103 participants with type 2 diabetes, who were randomly allocated in blocks matched by glycated hemoglobin and sex, by control group (n = 56) and experimental group (n = 47). Data collection was performed from December 2017 to May 2018. In the recruitment, the participants were informed about the study protocol and measureds about exclusion criteria and adherence to the pharmacological treatment were evaluated, as well as the collection for the biochemical data. At the subsequent meeting, socioeconomic, clinical and anthropometric data were collected and the intervention was started with monthly follow-up for three months. The experimental group consumed a pill containing 600 milligrams of ginger 0.1% dry extract, twice daily, and control group received pills of ginger containing microcrystalline cellulose MC-102. Data analysis was performed using SPSS 22.0, software R 3.3.1., And U-tests of Mann-Whitey, Wilcoxon, Pearson's Chi-square and Fischer's exact test. The study was approved by the Research Ethics Committee of the State University of Piauí (number: 2.248.450) and registered in the Brazilian Network of Clinical Trials (TRIAL: U111-1202-1650). The results indicate the prevalence of women, the time of diagnosis <5 years and the presence of hypertension. The most of the participants were sedentary, overweight and high levels of glycemia and lipids. Ginger significantly reduced fasting blood glucose (p=0,001), cholesterol (p=0,010), and LDL-C (p=0,018) in the experimental group compared to baseline, however, there was no significant reduction in control group (-29,55 ± 53,76 vs. -9,25 ± 48,44, p=0,13), (-11,62 ± 30,5 vs. -8,09 ± 75,32, p=0,884) and (-7,45 ± 23,12 vs. 11,97 ± 66,15, p=0,12), respectively. Diagnostic time had a significant association with glycemia, age with glycemia, HDL-C, LDL-C and HOMA-IR, and waist circumference with HDL-C and HOMA-IR. The ginger can be considered an adjuvant therapy for type 2 diabetes, since it has reduced some glycemic and lipemic parameters.